Chasing the zone: Reduced beta power predicts baseball batting performance. (1st November 2018) - Pluta, Anthony; Williams, Chad C.; Binsted, Gordon; Hecker, Kent G.; Krigolson, Olave E.
Highlights: Beta band EEG power predicts baseball batting performance. Demonstrates use of mobile EEG. Provides insight in performance prediction. Beta power reflective of the "sports zone". Abstract: Mental state prior to sports skill execution is related to subsequent performance. For example, relationships between pre-performance electroencephalogram (EEG) power and subsequent movement outcomes in golf putting, pistol shooting, and basketball free throw shooting have been previously reported. With that said, the existing body of research examining the pre-performance EEG – performance relationship has been focused on the execution of internally as opposed to externally-paced motor skills. Given that the execution of internally and externally-paced movements are dependent on different neural pathways, in the present study we examined whether or not pre-performance EEG power predicted ensuing performance of an externally-paced motor skill – baseball batting. Sixty-seven baseball players had EEG data recorded for 120 s prior to batting practice. Performance was assessed by three expert coaches and the accuracy of coach performance ratings was verified via Generalizability Theory. An analysis of our data revealed an inverse relationship between frontal EEG power in the beta range and subsequent batting performance - reduced beta power was associated with better batting performance whereas increased beta power was associated with worse batting performance. Our results are in line with prior research that has demonstrated a relationship between increased EEG power in the beta range and the subsequent commitment of motor errors in addition to the aforementioned work examining pre-performance EEG and the execution of internally-paced motor skills.